Sensory acceptability of the whole wheat and flaxseed (Linum usitatissimum L.) flours-added pizza dough among adolescent customers - Russo, Camila Bossoni (2012)
Flaxseed is an ingredient widely used in food products such as breads, biscuits and pasta in general, due to its beneficial components. The objective of this study was to develop pizza dough enriched with whole wheat and flaxseed flours, and to assess its sensory acceptability among adolescents, as well as to perform the physicochemical composition analysis of the standard formulation and most accepted containing flaxseed. Five salty pizza dough formulations were prepared, being one standard (FS) and the other containing different proportions of flaxseed flour: 2.5% (F1), 5.0% (F2), 7.5% (F3) and 10.0% (F4). No significant differences were found among the samples for appearance, aroma and flavor attributes, and in a general way the F2 and FS formulations got higher acceptability scores than F3, with no difference in the others. FS and F4 formulations were scored a higher buying intention than F3 (p < 0.05). By adding flaxseed into the formulations, the protein, fat and crude fiber contents increased (p < 0.05). It is feasible to add the whole wheat flour and the linseed into the pizza dough formulations, seeing that the results were satisfactory and they were well accepted by consumers, representing a more nutritious and palatable food option for adolescents.